Penerapan Strategi Peer Lesson Untuk Meningkatkan Hasil Belajar Al-Qur’an Hadist Pada Peserta Didik - Muliyani, Muliyani; Sitti Aisyah; Kholida, Leliy (RELIGI: Jurnal Pendidikan Agama Islam, 2025)
The purpose of this study is to find out the application of peer lesson strategies to improve the learning outcomes of the Qur'an Hadith in grade VII students at MTsN 1 Konawe, Tangkombuno Wawonii Islands, Northeast. This type of research is class action research or PTK which is carried out in two cycles, each cycle consists of two meetings, each cycle consists of 4 stages, namely Planning, Implementation of Actions, Observation and Reflection. The results of the study explained that 1) The application of this peer lesson strategy can improve the learning outcomes of students in the subject of Al-Qur'an Hadith at MTsN 1 Konawe Islands, it can be seen from the stage of implementation of learning analysis that the researcher got from the implementation stage is that from the first meeting to the last meeting, all students in the experimental class are very enthusiastic and enthusiastic to participate in the learning activities that are Implemented. Based on the results of the research that has been carried out, in the pre-cycle there are 4 students or 33% who have reached the KKM while there are 8 students or 66% who have not reached the KKM. Then in the implementation of cycle 1 there were 7 students or 58% who had reached KKM while there were 5 students or 41% who had not reached KKM in the implementation of cycle 2 there were 11 students or 91% who had reached KKM while there was one student or 8% who had not reached KKM with the results of the indicator research having reached 95% so that this research was declared successful